Volumetric models for quantifying the wood volume of two eucalyptus hybrids in an agrosilvipastoral system - Borges, Wander Luis Barbosa; de Freitas, Rogério Soares; da Silva, Giane Serafim; Silvestre, Marcela Aparecida De Moraes [UNESP]; de Moraes, Mario Luiz Teixeira [UNESP] (Southern Cross Publishing, 2023)
Quantifying the wood volume of forest stands is essential for planning sustainable forest management. The most efficient means of quantifying wood volume is volumetric equations. Many models for adjusting volumetric equations have been developed and tested, but their suitability for agrosilvipastoral systems remains unclear. To address this gap, we assessed the ability of six volumetric models to generate estimates of the total volume with bark of eucalyptus hybrids Grancam 1277 and Urograndis H-13. The trees were cultivated in an agrosilvipastoral system in an Arenic Hapludult in the municipality of Votuporanga, São Paulo State, Brazil, which is within the Cerrado biome. For Urograndis H-13, the Takata model was most accurate for quantifying volume, as it gave the highest F test (178.38) and adjusted coefficient of determination (0.93) values and the smallest standard error (0.06). The nonlinear and linear Schumacher-Hall models were most accurate for Grancam 1277, as this model gave the highest F test (54.59) and adjusted coefficient of determination (0.8) values and the smallest standard error (0.07).
Keywords: agroforestry; crop systems; intercropping systems; other models; statistics